Dakilang ina a celebration of Marian songs [soundrecording] - Hermano, Teresita Z.; Salvador, Eva G. (Manila Communications Foundation for Asia, Electronic Media Division)
A celebration of Marian songs, all of which are original prize winning compositions. Sung by various artists.
Magpuri't umawit -- Sa reyna ng langit -- Maria, aming ina -- Hiyas ng buhay -- Aba Ginoong Maria -- Aking ina, aking huwaran -- Flores de Mayo -- Milagrosang ina -- Hirang ng Diyos -- Canticle of Our Lady -- Birheng Maria -- Ulirang Ina -- Dakilang ina -- Magpuri'y umawit (Reprise).
Arrangers: Rene Ongpauco, Fr. Eduardo Hontiveros, S.J.
Keywords: Mary, Blessed Virgin -- Saint; Marian songs; Music